Circulation of Tc Ia discrete type unit Trypanosoma cruzi in Yucatan Mexico (2016)
ABSTRACT: The etiologic agent Trypanosoma cruzi (Tc) has been grouped into six discrete type units (DTU I-VI); within DTU-I exists four subgroups defined Ia-Id. In Colombia, the genotype Ia is associated with human infection and domiciled Rhodnius vector. In the Yucatan Peninsula of Mexico, the main vector involved in T. cruzi transmission is Triatoma dimidiata predominantly via sylvatic and peridomiciliated cycles. In this study, multiple sequence analysis of mini-exon intergenic regions of T. cruzi isolates obtained from T. dimidiata in the Yucatan Peninsula of Mexico revealed they belonged to Tc Ia DTU along with two additional Mexican strains located 1,570 km away from Yucatan. In conclusion Tc Ia circulates in the Yucatan peninsula in T. dimidiata vector and likewise in the northwest region of Mexico.